Prediction of ball direction in soccer penalty through kinematic analysis of the kicker - Secco Faquin, B.; Teixeira, L. A.; Coelho Candido, C. R.; Boari Coelho, D.; Bayeux Dascal, J.; Alves Okazaki, V. H. (Journal of Sports Sciences, 2023)
The penalty kick is a crucial opportunity to score and determine the outcome of a soccer match or championship. Anticipating the direction of the ball is key for goalkeepers to enhance their defensive capabilities, considering the ball's swift travel time. However, it remains unclear which kinematic cues from the kicker can predict the ball's direction. This study aimed to identify the variables that predict the ball's direction during a soccer penalty kick. Twenty U19 soccer players executed penalty kicks towards four targets positioned in the goal, while kinematic analysis was conducted using a 3D motion analysis system. Logistic regression analysis revealed that trunk rotation in the transverse plane (towards the goal - left; or slightly to the right - right) served as the primary predictor of the ball's horizontal direction at 250 and 150 ms before the kicking foot made contact. Additionally, the height of the kicking foot in the sagittal plane solely predicted the vertical direction at the moment of contact. This information, encompassing trunk rotation and kicking foot height, can be employed in perceptual training to enhance decision-making and the implementation of feints during penalty kicks.